THE RELATIONSHIP BETWEEN LEGAL KNOWLEDGE AND ATTITUDE TOWARD JUSTICE OF THE PARTICIPANTS IN COMMUNITY KNOWLEDGE SHARING PROJECT, SRI CHAROEN VILLAGE, NONGKHAI PROVINCE - Buchitchon, Suntaree; Tungsungnain, Ussanee (PEOPLE: International Journal of Social Sciences, 2015)
The research aims to study the correlation between legal knowledge and the attitude toward justice of the law. The sample of this research consists of 40 participants in Community Knowledge Sharing Project which was conducted in Sri Charoen Village, Nong Khai Province in 2015. The data of legal knowledge and attitude toward justice were collected before and after the knowledge sharing project. The statistics used to analyze the data were percentage, mean, standard deviation, t-test and Pearson’s correlation. The result shows that the level of knowledge and attitude before the knowledge sharing project were at low level and were increased to high level after the knowledge sharing project. Furthermore, the research shows that there are correlation between legal knowledge and attitude toward justice of the law.